2021
DOI: 10.3390/metabo11070436
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antioxidant and Antimutagenic Properties of Red and White Wine Extracts In Vitro

Abstract: Wine is an alcoholic beverage of complex composition obtained through the fermentation of grape must. The consumption of wine has already been associated with a multitude of beneficial effects due to its high polyphenolic content. In this study, four Greek emblematic wines from two red (i.e., Xinomavro and Agiorgitiko) and two white (i.e., Assyrtiko and Malagouzia) varieties were analyzed for the estimation of their antioxidant profiles. To address this question, we assessed their ability to scavenge both synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 96 publications
(113 reference statements)
0
16
0
5
Order By: Relevance
“…Only an ethanolic solution of rutin at the concentration of 830 µM prolonged the aPTT, while the TT and PT were unaffected [69]. According to the results obtained and based on numerous recent reports [7,[66][67][68][69], it was declared that wines possess a high bioactivity that allows them to be settled in the industries of food additives and medicinal products. In addition to phenolics, a number of other compounds are responsible for the quality of wine, as they determine the overall organoleptic impression of the wine in addition to the content of phenolic compounds, which are also present in large amounts in many other food products.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Only an ethanolic solution of rutin at the concentration of 830 µM prolonged the aPTT, while the TT and PT were unaffected [69]. According to the results obtained and based on numerous recent reports [7,[66][67][68][69], it was declared that wines possess a high bioactivity that allows them to be settled in the industries of food additives and medicinal products. In addition to phenolics, a number of other compounds are responsible for the quality of wine, as they determine the overall organoleptic impression of the wine in addition to the content of phenolic compounds, which are also present in large amounts in many other food products.…”
Section: Discussionmentioning
confidence: 78%
“…Wine phenolics inhibited CRP expression [14]. Oversimplifications of the above results were indicated in reports [2,7,14] that the consumption of antioxidant-/polyphenolrich foods might, therefore, impart anti-thrombotic-and cardiovascular-protective effects via their inhibition of platelet hyperactivation or aggregation. As a result of the ability of polyphenols to target additional pathways of platelet activation, they may have the potential to substitute or complement currently used anti-platelet drugs in sedentary, obese, pre-diabetic, or diabetic populations who can be resistant or sensitive to pharmacological anti-platelet therapy [2].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Peroxyl radical-induced DNA plasmid strand cleavage. Τhe assay was performed with some modifications, as previously described by Tekos et al (43). The thermal decomposition of the 2,2'-azobis(2-amidinopropane) dihydrochloride (aaPH) creates peroxyl radicals (ROO•).…”
Section: Methodsmentioning
confidence: 99%
“…Xinomavro is an emblematic Greek red wine produced from a red grape variety planted mainly in Central and Northern Greece. The assessment of the antioxidant capacity of a wine extract derived from Xinomavro by a recent study of our research group has demonstrated that the wine extract contains high levels of polyphenolic compounds and exerts strong antioxidant and antimutagenic activities in in vitro cell-free systems [ 49 ]. Therefore, the elucidation of its bioactivity at higher levels of complexity, i.e., cell-based and in vivo systems, could provide valuable insights into its potential applications in the food and pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%